Why Study Talmud in the Twenty-First Century?: The Relevance of the Ancient Jewish Text to Our World - Socken, Paul (Lexington Books, 2009)
The Talmud is the repository of thousands of years of Jewish wisdom. It is a conglomerate of law, legend, and philosophy, a blend of unique logic and shrewd pragmatism, of history and science, of anecdotes and humor. Unfortunately, its sometimes complex subject matter often seems irrelevant in today's world. In this edited volume, sixteen eminent North American and Israeli scholars from several schools of Jewish thought grapple with the text and tradition of Talmud, talking personally about their own reasons for studying it. Each of these scholars and teachers believes that Talmud is indispensible to any serious study of modern Judaism and so each essay challenges the reader to engage in his or her own individual journey of discovery. The diverse feminist, rabbinic, educational, and philosophical approaches in this collection are as varied as the contributors' experiences. Their essays are accessible, personal accounts of their individual discovery of the Talmud, reflecting the vitality and profundity of modern religious thought and experience.